2007
DOI: 10.1111/j.1095-8649.2007.01438.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and histochemical study on the intestinal mucosa of the common carp Cyprinus carpio L., with special consideration of mucin glycoproteins

Abstract: The biochemical and histochemical properties of intestinal mucin glycoproteins of virus and parasite-free common carp Cyprinus carpio were investigated. The presence of carbohydrates in mucin glycoproteins could be demonstrated by histochemical methods, but generally, no obvious differences in specific staining for mucin glycoproteins were observed in contrast to biochemical techniques. Biochemical staining methods displayed differences in structure and composition of intestinal glycoproteins. Released intesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 28 publications
2
38
0
2
Order By: Relevance
“…Herein, it was reported that the expression of MUC2 increased directly with the increase of β-glucans in the diet, which might suggest that the ability to regulate the expression of mucin is a benefit for responding to pathogens. However, a decrease in expression was observed in A. tropicus fed 2.0% β-glucans in the diet, which indicated that high concentrations of this immunostimulant inhibited the expression of MUC2 (a quadratic response), which is in accordance with reports in C. carpio, where the increase in the mucus layer, rich in oligosaccharide-modified glycoproteins was observed with the administration of this immunostimulant [49]. Likewise, studies in mammals, evaluating galactooligosaccharides and fructooligosaccharides, reported a positive effect on the mucin content in the intestinal mucosa [50,51].…”
Section: Discussionsupporting
confidence: 80%
“…Herein, it was reported that the expression of MUC2 increased directly with the increase of β-glucans in the diet, which might suggest that the ability to regulate the expression of mucin is a benefit for responding to pathogens. However, a decrease in expression was observed in A. tropicus fed 2.0% β-glucans in the diet, which indicated that high concentrations of this immunostimulant inhibited the expression of MUC2 (a quadratic response), which is in accordance with reports in C. carpio, where the increase in the mucus layer, rich in oligosaccharide-modified glycoproteins was observed with the administration of this immunostimulant [49]. Likewise, studies in mammals, evaluating galactooligosaccharides and fructooligosaccharides, reported a positive effect on the mucin content in the intestinal mucosa [50,51].…”
Section: Discussionsupporting
confidence: 80%
“…The presence of PAS positive mucous cells suggests transport of molecules across the cell membrane. The strong AB positive mucous cells at the base of the main pancreatic duct mucosal fold may suggest and adaptation for protection against pathogens as more bacteria may accumulation at this location more than at the tip [31].…”
Section: Discussionmentioning
confidence: 99%
“…Adhesion was expressed as the percentage of fluorescence recovered in the second measurement relative to the fluorescence at T0. Binding of the mucus to the plate was confirmed by a lectin-binding assay as described by Neuhaus et al (2007), using Dolichos biflorus lectin (DBA, Sigma).…”
Section: Bacteria and Saprolegnia Isolates And Skin Mucusmentioning
confidence: 99%